Interferon-gamma release assay and chest X-ray to classify intraocular tuberculosis among clinically undifferentiated uveitis (Faculty of Medicine Universitas Indonesia, 2022)
BACKGROUND Tuberculosis (TB) is a common cause of intraocular inflammation in Indonesia. As no accurate biomarker can confirm the diagnosis, ophthalmologists often rely on systemic findings, such as tuberculin skin test, interferon-gamma release assay (IGRA), and chest X-ray (CXR) for TB suspicion. This study aimed to evaluate IGRA and CXR in classifying intraocular TB among patients with a clinically undifferentiated cause of uveitis. METHODS This cross-sectional study included 116 patients (a total of 163 affected eyes) with a clinically undifferentiated cause of uveitis. IGRA and CXR were performed as part of the workup. Data on visual acuity, anterior chamber inflammation grade, and anatomical classification of uveitis were recorded. As there were no confirmed ocular tuberculosis (OTB) in our cases, eyes were classified into probable OTB, possible OTB, and unclassified. RESULTS Overall, 93 patients (80.2%) with a clinically undifferentiated cause of uveitis had positive IGRA, whereas 10 (8.6%) had CXR results suggestive of TB. More than one-third of the patients were blind (visual acuity <3/60), and panuveitis was the commonest anatomical classification. A trend was identified in patients with panuveitis, who often showed ≥2+ cell anterior chamber inflammation (p for trend = 0.023), according to OTB criteria (probable OTB = 3/4, 75.0%; possible OTB = 44/67, 65.7%; unclassified = 2/9, 22.2%). Furthermore, the clinically undifferentiated uveitis cases were eligible to be stratified into probable (8.6%) and possible (75.0%) OTB categories after IGRA and CXR examinations. CONCLUSIONS The combination of IGRA and CXR is valuable for classifying and diagnosing TB-related uveitis. A multidisciplinary approach is essential when the cause of uveitis is unknown.